The Concept Of Zakat In The Qur'an As Wealth Redistribution And Motivation For Building Social Welfare - Nuradi, Nuradi; Khatimah, Husnul; Alim, Akhmad; Muhammad, Salihu Musa Jibo (ZAD Al-Mufassirin, 2025)
This study aims to analyze the concept of zakat in the Qur'an as an instrument of wealth redistribution and social welfare programs, and explore its role in reducing social inequality and poverty in Islamic society. This type of research is a qualitative approach with literature research. Data collection is carried out through literature review of various Qur'anic verses consisting of related zakat issues. The research results show that zakat plays an important role in maintaining economic balance by channeling wealth from the wealthy to the needy. In addition, zakat in the Qur'an serves as a comprehensive solution for poverty alleviation, while strengthening social solidarity, and creating a more inclusive and prosperous society.  In terms of social welfare motivation, it is mentioned in several verses, such as supporting the collective welfare of Al-Hasyr verse 7, empowering vulnerable groups Ad-Dhuha verses 9-10, promising good rewards in the hereafter for those who care about the welfare of others Al-Baqarah verse 261, and Adz-Zariyat verse 19. Thus, the concept of zakat in the Qur'an is not only a religious obligation, but also a comprehensive framework for upholding social justice, reducing inequality, and promoting inclusive economic welfare.